Age-Related Hearing Loss, Late-Life Depression, and Risk for Incident Dementia in Older Adults. (22nd September 2020) - Brewster, Katharine K; Hu, Mei-Chen; Zilcha-Mano, Sigal; Stein, Alexandra; Brown, Patrick J; Wall, Melanie M; Roose, Steven P; Golub, Justin S; Rutherford, Bret R
Abstract: Background: Hearing loss (HL), late-life depression, and dementia are 3 prevalent and disabling conditions in older adults, but the interrelationships between these disorders remain poorly understood. Methods: N = 8529 participants ≥60 years who were free of cognitive impairment at baseline were analyzed from National Alzheimer's Coordinating Center Uniform Data Set. Participants had either No HL, Untreated HL, or Treated HL. Primary outcomes included depression (15-item Geriatric Depression Scale ≥5) and conversion to dementia. A longitudinal logistic model was fit to examine the association between HL and changes in depressive symptoms across time. Two Cox proportional hazards models were used to examine HL and the development of dementia: Model A included only baseline variables and Model B included time-varying depression to evaluate for the direct effect of changes in depression on dementia over time. Results: Treated HL (vs no HL) had increased risk for depression (odds ratio [OR] = 1.26, 95% confidence interval [CI] = 1.04–1.54, p = .02) and conversion to dementia (hazard ratio [HR] = 1.29, 95% CI = 1.03–1.62, p = .03). Baseline depression was a strong independent predictor of conversion to dementia (HR = 2.32, 95% CI = 1.77–3.05, p < .0001). Development/persistence of depression over time was also associated with dementia (HR = 1.89, 95% CI = 1.47–2.42, p < .0001), but only accounted for 6% of the direct hearing–dementia relationship (Model A logHR = 0.26 [ SE = 0.12] to Model B logHR = 0.24 [ SE = 0.12]) suggesting no significant mediation effect of depression. Conclusions: Both HL and depression are independent risk factors for eventual conversion to dementia. Further understanding the mechanisms linking these later-life disorders may identify targets for early interventions to alter the clinical trajectories of at-risk individuals.